Suppression of progesterone synthesis in human trophoblast cells by fine particulate matter primarily derived from industry. (December 2017) - Wang, Cui; Yang, Jinhuan; Hao, Zhengliang; Gong, Chenxue; Tang, Lihua; Xu, Yingling; Lu, Dezhao; Li, Zhuoyu; Zhao, Meirong
Abstract: Epidemiological studies have exhibited a positive association between fine particulate matter (PM2.5 ) exposure and adverse pregnancy outcome (APO). However, source-related effect and the potential mechanism have not been thoroughly elucidated in toxicology. In this study, PM2.5 was collected during a severe winter haze episode in an energy-base city of China. We coupled this approach with the source appointment by applying the Lagrangian Integrated Trajectory and Concentration Weighted Trajectory model. We observed that the primary trajectory with high polluted air mass came from the northwest of the sampling site. Approximately 90% or more of PM2.5 was derived from the industry at this haze period. Next, the sampled PM2.5 was used to study the classical hormone synthesis pathway on trophoblast JEG-3 cells. PM2.5 induced the secretion of human chorionic gonadotrophin (HCG) and the proliferation of JEG-3 cells at a noncytotoxic concentration. However, the synthesis of progesterone was significantly suppressed, even if both hCG and cyclic adenosine monophosphate (cAMP) were increased, suggesting that PM2.5 may interfere the downstream of cAMP. As expected, the phosphorylated activity of protein kinase A (PKA) was attenuated. Subsequently, the downstream molecules of steroidogenesis, such as ferredoxin reductase (FDXR), CYP11A1 (encoded P450scc), and 3β-Hydroxysteroid dehydrogenase type 1 (3β-HSD1), were inhibited. Therefore, PM2.5, primarily derived from industry, may directly inhibit the phosphorylation status of PKA in JEG-3 which, in turn, inhibited the proteins expression in progesterone-synthesis to suppress progesterone levels. Considering the pivotal role of progesterone in pregnancy maintenance, the mechanism on hormone synthesis may provide a better understanding for PM2.5 -caused APO. Industry-emanated PM2.5, though not specific, could threaten the placenta, which needs to be verified by further epidemiological studies. Graphical abstract: Highlights: The hybrid receptor model indicated the source of PM2.5 primary derived from industry. PM2.5 induced hCG and cAMP while inhibited the phosphorylation of PKA and the downstream molecular. Industry-derived PM2.5 inhibit the synthesis of progesterone in JEG-3 cells. Abstract : The industry-derived PM2.5, which identified by the hybrid receptor model, disturb the progesterone synthesis through inhibiting the activity of PKA and its downstream.